Proses Pembelajaran Tahfidz Alquran Terhadap Peserta Didik - Anwar Fuadi Jalil; Alfurqan Alfurqan (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to: Knowing the process of learning tahfidz in improving the ability to memorize the Koran in class VI Khaira Ummah Islamic Elementary School, Padang City. To achieve the above objectives, a qualitative approach with the type of field research is used. Based on the results of observations, the author has determined that the informants who will be the main data sources in this study are 10 informants. The 10 informants were 1 principal, 1 student representative, 1 administrative person, represented by 2 educators, and 5 students. The results of this study indicate that 1) The tahfidz learning process in improving the ability to memorize the Koran in students at the Khaira Ummah Islamic Elementary School 2) Supporting and inhibiting factors for the tahfidz al-Quran learning process 3) Tahfidz learning solutions to overcome obstacles in memorizing the Koran. The benefits of this research are as follows: 1) Theoretical benefits are expected to be able to contribute to educational practitioners in providing scientific input related to the object of research and to increase the knowledge of Islamic religious education 2) Practical benefits, for institutions to improve teaching strategies in the learning process. memorizing the Koran and for schools as an evaluation and input for the school.